2015
DOI: 10.18488/journal.70/2015.2.1/70.1.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Rainfall and Temperature Variability to Guide Sorghum (Sorghum Bicolar) Production in Miesso Areas, Eastern Ethiopia

Abstract: Assessment of climate variability at local level has enormous advantage in Ethiopia, where the driver of the economy is agriculture. This study was conducted to analysis rainfall and temperature variability to guide sorghum production in Miesso. Daily climate data was obtained from the National Meteorological Service Agency of Ethiopia (NMA). Temporal rainfall variability was assessed through the timing of onset date, end date, length of growing season and dry spell length using INSTAT climate guide. Temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
(4 reference statements)
2
3
0
Order By: Relevance
“…A significant increase in temperature and rainfall variability has been reported in different parts of Ethiopia ( Hayelom et al., 2017 ; Tamiru et al., 2015 ), which is in line with our results. However, the significant decline of rainfall in the mRS and especially in the lowland part of the ARB was a novel finding in our case.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…A significant increase in temperature and rainfall variability has been reported in different parts of Ethiopia ( Hayelom et al., 2017 ; Tamiru et al., 2015 ), which is in line with our results. However, the significant decline of rainfall in the mRS and especially in the lowland part of the ARB was a novel finding in our case.…”
Section: Resultssupporting
confidence: 93%
“…Change-point detection of climate data have been performed using Buishand's range (BR), standard normal homogeneity (SNH), Pettit's and the von Neumann ratio (VNR) tests besides to the trend analysis based on Mann-Kendall (MK) test ( Suhaila and Yusop, 2018 ; Onyutha, 2016 ; Javari, 2016 ; Jaiswal et al., 2015 ; Zarenistanak et al., 2014 ; Croitoru et al., 2012 ). The Manna Kendall Trend test of rainfall and temperature has been conducted in different part of Ethiopia ( Demissie and Sime, 2021 ; Wedajo et al., 2019 ; Samy et al., 2019 ; Elzeiny et al., 2019 ; Asfaw et al., 2018 ; Alemayehu and Bewket, 2017 ; Hayelom et al., 2017 ; Tamiru et al., 2015 ; Mengistu et al., 2014 ) and Awash river basin ( Shawul and Chakma, 2020 ; Mulugeta et al., 2019 ; Gedefaw et al., 2018 ; Bekele et al., 2017 ). These above several recent studies in Ethiopia showed a significantly increasing trend in temperature and an inconsistent trend in rainfall.…”
Section: Introductionmentioning
confidence: 99%
“…A signi cant increase in temperature and rainfall of variability has been reported in different parts of Ethiopia, which is in line with our results, but the signi cant decline of rainfall in the mRS and especially in the lowland part of the basin was a novel nding (Hayelom et al, 2017;Tamiru et al, 2015). A similar nding that mRS rainfall is more variable than the MRS rainfall has been reported in the northern part of The rainfall in mRS showed higher variability than in the MRS and annual that matches with our result (Tadese, et al, 2019).…”
Section: Trend Analysis and Coe Cients Of Variation (Cv)supporting
confidence: 92%
“…Increasing in extreme temperature can cause severe yield reduction, and subsequent negative impact in the reproduction stage of many crops (Hatfield and Prueger 2015;Thornton et al 2014). The rate of photosynthesis and transpiration processes can be hampered by changes in the weather extremes, for example, diurnal temperature variations (Tamiru et al 2015), and subsequent effects on crop water requirement and soil water balance. Besides, the western part of Tigray is an unexploited high agricultural production area; wshere, livestock production, crop production like sorghum, sesame and cotton crops; and boswellia (Boswellia papyrifera (Del)) Hochyst; as industrial tree for export purpose are commonly practiced.…”
Section: Discussionmentioning
confidence: 99%